Integration of Local Wisdom Mangrove Ecotourism in Class IV Learning in Elementary School - Asrial Asrial; Syahrial Syahrial; Maison Maison; Dwi Agus Kurniawan; Muhammad Toto Nugroho (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2021)
This article aims to integrate local wisdom of Mangrove Ecotourism in the learning process in elementary schools to meet the demands of the 2013 curriculum based on local wisdom. This type of research is descriptive qualitative research using ethnography. The research sample consisted of 7 informants, with two community leaders, two people from the Youth and Sports Tourism Office and three classroom teachers. This research, using instrument through observation, interviews, and documentation. The results of the study found that local wisdom of Mangrove Ecotourism can be applied in the learning process in grade IV elementary schools and can provide excellent benefits in the development of the developmental aspects of students not only in cognitive aspects but in affective and psychomotor aspects of students. Keywords: Local Wisdom , Ecotourism Mangrove, Learning Activity